ICT in Physical Education and E-Curriculum in Science Education - NWABUWE, Sunday Nathaniel; NWABUWE, Henrietta Ifeanyichukwu (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2024)
The integration of Information and Communication Technology (ICT) in education has revolutionized the teaching and learning process, particularly in physical education and science education. In physical education, ICT tools such as wearable devices, video analysis applications, and gamification platforms enhance student engagement and performance assessment, offering personalized learning experiences (Casey et al., 2017; Sargent & Casey, 2020). Similarly, in science education, e-curriculum has transformed traditional teaching methodologies by incorporating virtual simulations, interactive labs, and adaptive learning systems, enabling more effective and interactive learning environments (Rodriguez & Dyck, 2020; Smetana & Bell, 2020). The widespread use of these tools promotes personalized learning, collaboration, and active participation, ensuring a deeper understanding of both theoretical concepts and practical skills. However, the implementation of ICT in education also presents challenges such as unequal access to technology, the need for teacher training, and concerns about data privacy (UNESCO, 2022). Despite these barriers, the benefits of ICT-driven e-curriculum, including increased accessibility, flexibility, and engagement, highlight its transformative potential in modern education. To fully realize these benefits, it is crucial to address existing challenges through strategic investments in infrastructure, professional development, and ethical ICT use. Overall, ICT in physical education and e-curriculum in science education offer innovative ways to enhance learning outcomes and equip students with the skills necessary for success in the digital age.